Anglo-American naval relations, 1919-1939 - Simpson, Michael (Michael A.) (Burlington, VT : Ashgate for the Navy Records Society, 2010)
Those interested in Anglo America Naval Relations prior to the Second World War will benefit from this book. This volume brings together documents from the period 1919-1939 which was dominated by a series of naval arms limitation and disarmament conferences. The book also includes a section of documents that deal with encounters of serving officers and men of the two navies and their observations on each other's navy, while the final section details the hesitant and limited steps towards co-operation during 1937-1939 when the prospect of a second world war looked increasingly likely. Drawing on a wide range of documents from British and American archives, this volume provides a fascinating overview and insight into relations between the two navies during the interwar period. Contents: Preface; The Washington conference, 1919-1923; The Geneva conference, 1922-1927; The 1st London naval conference, 1927-1930; The 2nd London naval conference, 1930-1936; The sailors meet, 1919-1939; Edging towards an alliance, 1937-1939; List of sources and documents; Index.
The Washington Conference, 1919-1923 -- The Geneva Conference, 1922-1927 -- The First London Naval Conference, 1927-1930 -- The Second London Naval Conference, 1930-1936 -- The sailors meet, 1919-1939 -- Edging towards an alliance, 1937-1939.
Includes bibliographical references and index.
In English.
JSTOR
Keywords: United States. -- Navy -- History -- 20th century -- Sources; Great Britain. -- Royal Navy -- History -- 20th century -- Sources; Great Britain. -- Royal Navy; United States. -- Navy; United States -- Military relations -- Great Britain -- Sources; Great Britain -- Military relations -- United States -- Sources; États-Unis -- Relations militaires -- Grande-Bretagne -- Sources; HISTORY / Military / Naval; Military relations; Great Britain; United States; 1900-1999; Admiral Harry Yarnell; Admiral Sir Ernle Chatfield; Admiral William Leahy; Admiral William Pratt; Admiralty; Aircraft Carriers; Anglo-American relations; Atlantic Ocean; Australia; China; Europe: France; Franklin Roosevelt; Germany; Japan; Pacific Ocean; Rights at Sea; Royal Navy; The Interwar Years; United States; merchant shipping; submarines; History; Sources